Micropropagation of Dendrobium phalaenopsis Orchid Through Overexpression of Embryo Gene AtRKD4 - Setiari, Nintya; Purwantoro, Aziz; Moeljopawiro, Sukarti; Semiarti, Endang (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
To increase the efficiency of crop production from Dendrobium phalaenopsis orchids, mass propagation has been performed by inducing somatic embryogenesis through Agrobacterium-mediated transformation of the Arabidopsis embryo gene AtRKD4 into orchid protocorm (developing orchid embryo). The three-week-old protocorms of D. phalaenopsis were genetically transformed with T-DNA carrying 35S :: GAL4 :: AtRKD4 :: GR through A. tumefaciens strain EHA 105. The cultures were maintained in VW medium with 10 mg L-1 Hygromycin. Due to the existence of glucocorticoid response element (GR) in the T-DNA construct, the transformed protocorms were transferred into VW medium with the addition of 15 μM Dexamethasone in 6 weeks after transformation to activate the transgene. A total of 12% protocorms has been confirmed for Hyg + by using PCR. The expression of embryo gene AtRKD4 was confirmed by cDNA analysis using AtRKD4 specific primers and Actin primers as a positive control experiment. The expression level of AtRKD4 in 2.5-month-old D. phalaenopsis transformant shoots was 7 times higher than non-transformant plants, and increased to 86 times higher in 8-months, that much higher than that of non-transformant. These results provide an improved method for genetic transformation of D. Phalaenopsis and will (eventually) increase production efficiency in the future.